Pembiayaan Pendidikan di Era Otonomi Daerah: Studi Kasus di Kabupaten Solok - Putra, Ronni Ekha; Valentina, Tengku Rika (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2010)
In the current era of regional autonomy the financing of primary and secondary education becomes the responsibility of local governments. With its wide authority, local governments are required to be more creative and innovative in managing education. In order to obtain financing source other than the State and Local Budgets, local governments are expected to establish cooperation with the private sector or are entrepreneurs, so the partnership between private and government work well, and also the importance of community participation in the financing of education in accordance with the mandate of Law No. 20 of 2003 on national education system in which government, society and the private sectors is responsible to provide funding for education in the region. Â Kata Kunci : Pembiayaan Pendidikan, Otonomi Daerah, Desentralisasi Â